2017
DOI: 10.3892/or.2017.5996
|View full text |Cite
|
Sign up to set email alerts
|

Novel transduction of nutrient stress to Notch pathway by RasGRP3 promotes malignant aggressiveness in human esophageal squamous cell carcinoma

Abstract: In the process of enlarging of tumors, the dissolving tissue structures and remodeling endothelial cells for restoring gas exchange and nutritional support, further facilitate tumor cell invasion and metastasis. Activation of Ras plays a critical role in the development of esophageal squamous cell carcinoma (ESCC), but the underlying mechanisms remain poorly understood. We therefore investigated whether Ras guanyl-releasing protein 3 (RasGRP3), a Ras activator, could promote metastasis by inducing vascular reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…A previous study reported that SREBP1 can suppress VEGF expression through indirect interaction with the proximal tandem Sp1 sites in human smooth muscle cells (54). VEGF-C, as a lymphangiogenic switch, is a specific factor involved in the invasiveness and metastasis of ESCC (7,11,39,55). Furthermore, according to the significant relationship between SREBP1 expression levels and lymphatic metastasis shown in the present study, SREBP1 was identified as a promoting factor regulating VEGF-C formation and secretion.…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…A previous study reported that SREBP1 can suppress VEGF expression through indirect interaction with the proximal tandem Sp1 sites in human smooth muscle cells (54). VEGF-C, as a lymphangiogenic switch, is a specific factor involved in the invasiveness and metastasis of ESCC (7,11,39,55). Furthermore, according to the significant relationship between SREBP1 expression levels and lymphatic metastasis shown in the present study, SREBP1 was identified as a promoting factor regulating VEGF-C formation and secretion.…”
Section: Discussionsupporting
confidence: 65%
“…Tissue samples were collected during surgical resection after informed written consent had been provided by patients with ESCC (Table I). The patients were diagnosed by two pathologists in accordance with the World Health Organization classification without chemotherapy or radiotherapy before resection, as described previously (39). The 77 paired ESCC tumor and adjacent normal tissue samples that were 2 cm away from the tumors' edge, were collected between February 2018 and July 2019 at the Affiliated Hospital of Jiangsu University (Zhenjiang, China).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations